Liberation Hermeneutics in Religious Text Studies: A Phenomenological Analysis of Hasan Hanafi’s Thought at Lirboyo Islamic Boarding School - Rosyidah, Irma; Sari, Dewi Asri Fatma; Jazuli, Mohammad Hasan; Salik, Mohamad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The hermeneutics of liberation developed by Hasan Hanafi is an approach to interpreting religious texts that is more than just reading texts textually or normatively. Hasan Hanafi sees the holy texts of both the Qur'an and Hadith as dynamic sources that must be interpreted critically, relevant to the problems of the times and the conditions of society that are constantly changing. A progressive religious learning paradigm will be created by applying the hermeneutics of liberation at the Lirboyo Islamic Boarding School. The research method used is qualitative research with a phenomenological approach, with data collection through in-depth interviews and participatory observation. The research sample consisted of 5 Islamic Boarding School Ustadz, 2 of whom also taught as Lecturers at Ma'had Aly and 1 as the Head of Madrasah at the Lirboyo Islamic Boarding School, who were considered representative as research subjects to gain an in-depth understanding of the application of the research conducted. The results of the study indicate that liberation hermeneutics provides a potential critical and contextual perspective in responding to problems, but its implementation in the Lirboyo Islamic Boarding School environment is still limited by the strong dominance of the traditional method of the Syafi'I School which prioritizes textual and normative approaches. For this reason, more intensive efforts are needed to integrate the liberation hermeneutics perspective in order to provide a dynamic and adaptive contribution to change.